Role of the Stria Vascularis in the Pathogenesis of Sensorineural Hearing Loss: A Narrative Review - Yu, Wenting; Zong, Shimin; Du, Peiyu; Zhou, Peng; Li, Hejie; Wang, Enhao; Xiao, Hongjun (Frontiers in Neuroscience, 2021)
Sensorineural hearing loss is a common sensory impairment in humans caused by abnormalities in the inner ear. The stria vascularis is regarded as a major cochlear structure that can independently degenerate and influence the degree of hearing loss. This review summarizes the current literature on the role of the stria vascularis in the pathogenesis of sensorineural hearing loss resulting from different etiologies, focusing on both molecular events and signaling pathways, and further attempts to explore the underlying mechanisms at the cellular and molecular biological levels. In addition, the deficiencies and limitations of this field are discussed. With the rapid progress in scientific technology, new opportunities are arising to fully understand the role of the stria vascularis in the pathogenesis of sensorineural hearing loss, which, in the future, will hopefully lead to the prevention, early diagnosis, and improved treatment of sensorineural hearing loss.